2015
DOI: 10.1021/acsnano.5b07389
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Equilibrium Compositions in Colloidal Cd1–xMnxSe Nanocrystals Using Diffusion Doping and Cation Exchange

Abstract: The physical properties of semiconductor nanocrystals can be tuned dramatically via composition control. Here, we report a detailed investigation of the synthesis of high-quality colloidal Cd1-xMnxSe nanocrystals by diffusion doping of preformed CdSe nanocrystals. Until recently, Cd1-xMnxSe nanocrystals proved elusive because of kinetic incompatibilities between Mn(2+) and Cd(2+) chemistries. Diffusion doping allows Cd1-xMnxSe nanocrystals to be prepared under thermodynamic rather than kinetic control, allowin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(77 citation statements)
references
References 54 publications
3
74
0
Order By: Relevance
“…1(c), inset), it can be seen that the MneCdSe QDs have an average diameter of 6.1 ± 0.6 nm, which is slightly larger than that of 5.5 ± 0.7 nm of CdSe QDs. Recently, Gamelin et al have shown that the diameter of Mn 2þ doped CdSe nanocrystals can grow larger with the addition Mn 2þ precursors, which is consistent with our result [30]. The elemental analysis show in Fig.…”
Section: Resultssupporting
confidence: 91%
“…1(c), inset), it can be seen that the MneCdSe QDs have an average diameter of 6.1 ± 0.6 nm, which is slightly larger than that of 5.5 ± 0.7 nm of CdSe QDs. Recently, Gamelin et al have shown that the diameter of Mn 2þ doped CdSe nanocrystals can grow larger with the addition Mn 2þ precursors, which is consistent with our result [30]. The elemental analysis show in Fig.…”
Section: Resultssupporting
confidence: 91%
“…% Mn 2+ were realized. 28 It can be expected that with different synthesis methods also for CsPbCl 3 NCs, higher Mn 2+ doping levels are possible.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Doping of bulk materials is a very well developed field, which underpins most of our present technologies, since the properties of materials for lighting, electronic and optoelectronic applications are largely controlled by dopants. In contrast, the precise doping of NCs is still an underdeveloped field, which is however booming and has delivered great successes and many novel materials in recent years [28, 91100]. …”
Section: Excitons In Semiconductor Nanocrystalsmentioning
confidence: 99%